2008
DOI: 10.1614/wt-07-172.1
|View full text |Cite
|
Sign up to set email alerts
|

Response of Northeastern Arkansas Palmer Amaranth (Amaranthus Palmeri) Accessions to Glyphosate

Abstract: Palmer amaranth accessions were collected from 21 fields in northeastern Arkansas in the fall of 2006 to determine if they differed in response to increasing doses of glyphosate and to determine the survival frequency following treatment with the label rate (870 g ae/ha). The herbicide dose required to kill 50% of individuals in an accession (LD50) ranged from 41 to 339 g/ha glyphosate, with most accessions responding similarly to glyphosate. The AR18 and AR19 were the least-sensitive accessions, with LD50rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Palmer amaranth escapes following glyphosate applications could be associated with the species biology, especially the extended germination period which poses a challenge for glyphosate application timing . It has been reported that glyphosate control is reduced when plants are sprayed at later growth stages . The environmental conditions of central and southwestern Nebraska (predominant Palmer amaranth area) could also influence glyphosate performance.…”
Section: Resultsmentioning
confidence: 99%
“…Palmer amaranth escapes following glyphosate applications could be associated with the species biology, especially the extended germination period which poses a challenge for glyphosate application timing . It has been reported that glyphosate control is reduced when plants are sprayed at later growth stages . The environmental conditions of central and southwestern Nebraska (predominant Palmer amaranth area) could also influence glyphosate performance.…”
Section: Resultsmentioning
confidence: 99%
“…The advent of GR crops reduced diversification in alternative herbicide usage owing to glyphosate's broad spectrum of weed control. On the positive side, glyphosate applied PRE and post‐emergence (POST) in GR crops have been an important tool in curbing the rate of selection and spread of many weed biotypes with evolved resistance to other herbicides, especially ACCase and ALS inhibitors 29–32. However, the overreliance on glyphosate to control herbicide‐resistant weeds contributed to the evolution of multiple resistance in populations (i.e.…”
Section: Glyphosate‐resistant Weeds: History Mechanisms Genetics Anmentioning
confidence: 99%
“…Selection experiments repeated in time and place by conducting one experiment under controlled growth room conductions and one in field conditions showed the same evolution of glyphosate resistance and concomitant reduced paraquat sensitivity (Tables 1 and 2). Thus, genetic variability for reduced sensitivity to any particular herbicide can be rapidly selected within small populations of cross-pollinated species to result in population shifts towards higher levels of resistance (Neve and Powles 2005;Norsworthy et al 2008). The same phenomenon can equally occur under controlled and commercial field conditions.…”
Section: Paraquat Reduced Sensitivity Of Outdoor Field-grown Plantsmentioning
confidence: 99%